Español - Español, Español; Español, Español; Español, Español (Ars Pharmaceutica (Internet), 1991)
Reclaimed municipal wastewater from the argiva treatment plant can be used, without restrictions, for agricultural irrigation, because of its low concentracion of salts, toxic elements and suspended solids. Its application to the soil-plant system in a greenhouse experiment increased electrical conductivity of the saturated extract of the soil, and levels of Na and B in soil anct plant. However, no adverse effect was observed in a tomato crop.